2007
DOI: 10.1136/hrt.2006.096370
|View full text |Cite
|
Sign up to set email alerts
|

Impact of arterial remodelling and plaque rupture on target and non-target lesion revascularisation after stent implantation in patients with acute coronary syndrome: an intravascular ultrasound study

Abstract: In patients with ACS, PR and intravascular ultrasound findings that may correspond with plaque rupture predict cardiac events including both TLR and non-TLR at 2 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…This is quite in concordance with previous coronary IVUS studies. 8,18 However, this result should be carefully interpreted. The difference mainly comes from the higher incidence of unplanned vascular interventions because of nontarget lesion progres- sion or target lesion restenosis in patients with plaque rupture in the iliofemoral arteries than in patients without plaque rupture.…”
Section: Okura Et Al Plaque Rupture In Peripheral Artery Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…This is quite in concordance with previous coronary IVUS studies. 8,18 However, this result should be carefully interpreted. The difference mainly comes from the higher incidence of unplanned vascular interventions because of nontarget lesion progres- sion or target lesion restenosis in patients with plaque rupture in the iliofemoral arteries than in patients without plaque rupture.…”
Section: Okura Et Al Plaque Rupture In Peripheral Artery Diseasementioning
confidence: 99%
“…3 Plaque rupture was defined as the presence of a cavity that communicated with the lumen with an overlying residual fibrous cap fragment. 3,18 IVUS measurements were performed at the narrowest cross-sections in the target segment. IVUS measurements were also performed at the nonsignificant or nontarget cross-sections with plaque rupture in the iliofemoral arteries.…”
Section: Qualitative and Quantitative Ivus Analysesmentioning
confidence: 99%
“…[5][6][7]28,35,36 Furthermore, previous IVUS studies have consistently demonstrated that lesions with positive remodeling were associated with worse clinical outcomes. 15,19,36 -40 In our present study population, 12-month clinical follow-up did not show any prognostic impact of the arterial and fibrous cap remodeling because of the small sample size and short follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Schoenhagen et al cations. Moreover, in a study in 137 patients who presented with acute coronary syndromes, the presence of expansively remodeled lesions before stenting was predictive for the occurrence of cardiac events and lesion revascularization at 2 years (9). On the other hand, however, in the same aforementioned substudy of the REVERSAL trial it was also shown that the mode of arterial remodeling (expansive or constrictive) was not related to a change in atheroma volume comparing serial ultrasound data at baseline and follow-up (10), suggesting that the mode of geometrical remodeling cannot serve as an alternative surrogate measure for plaque progression over time.…”
Section: See Page 1708mentioning
confidence: 98%